The impacts of perceived access to public open spaces on non-physical wellbeing: focused on international graduate students in Seoul - Odilia Renaningtyas Manifesty; Gunwon Lee (Journal of Asian Architecture and Building Engineering)
The growing trend of international student mobility in Asia and the associated challenges, advocating for the use of public open spaces to enhance students’ wellbeing. Using a case study of Seoul, South Korea, this research offers an investigation into the interplay between access to these spaces and the non-physical wellbeing of international graduate students. It primarily contrasts perceived access and the actual frequency of visits to these spaces. Variables derived from literature were compiled into a questionnaire in which then was analyzed with both descriptive and inferential statistics. The study underscores the pivotal role of perceived access to public open spaces both in the city context and campus context, in enhancing the non-physical, highlighting the need for urban planning to prioritize quality access and awareness over mere frequency of visits. This study also emphasizes on the importance of perceived scale, safety, beauty, and ambiance attributes in moderating the positive impact of access to public open spaces. This result emphasizes on spaces that are not only physically accessible but also psychologically inviting and culturally resonant. This finding challenges the traditional focus on the quantitative expansion and underscoring the importance of perceived access for creating inclusive urban environments for an educational hub.